Design of a Broadband Polarization Splitter Based on Anisotropy-Engineered Tilted Subwavelength Gratings - Alaine Herrero-Bermello; Jose Manuel Luque-Gonzalez; Aitor V. Velasco; Alejandro Ortega-Monux; Pavel Cheben; Robert Halir (IEEE Photonics Journal)
Polarization management is of paramount importance in integrated optics, particularly for highly birefringent photonic platforms such as silicon-on-insulator. In this paper, we present a polarization beam splitter based on a multimode interference coupler incorporating tilted subwavelength gratings. The tilt provides accurate control of the structural anisotropy and enables independent selection of the beat length for two orthogonal polarization states. As a result, device length is reduced to less than 100 $μ$ m while simultaneously achieving broadband operation through subwavelength grating dispersion engineering. Insertion losses below 1 dB and an extinction ratio higher than 20 dB are demonstrated through three-dimensional FDTD simulation in a 131-nm bandwidth.